2022
DOI: 10.1007/s11205-021-02835-z
|View full text |Cite
|
Sign up to set email alerts
|

Urbanity, Neighbourhood Characteristics and Perceived Quality of Life (QoL): Analysis of Individual and Contextual Determinants for Perceived QoL in 3300 Postal Code Areas in Finland

Abstract: This analysis examines the geography of subjective wellbeing within a single country via a novel dataset consisting of more than 26,000 respondents embedded in 3100 postal code areas in Finland. We include a detailed indicator on the level of urbanity of the respondent’s location derived from a 250 × 250 m GIS grid, contextual measures of the postal code area´s socioeconomic status as well as proximity to the nearest urban locality and capital city. This analytical framework model makes it possible to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Studies that merely focus on objective environmental indicators do not take the importance of such subjective evaluations into account. Some studies investigate a direct link between objective living conditions and well-being on one hand, but additionally include subjective characteristics as potential factors (e.g., Ettema & Schekkerman 2016 ; Weckroth et al, 2022 ). Others conceptualise the relationship between objective living conditions and SWB indirectly by including subjective evaluations of these conditions (McCrea et al, 2006 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that merely focus on objective environmental indicators do not take the importance of such subjective evaluations into account. Some studies investigate a direct link between objective living conditions and well-being on one hand, but additionally include subjective characteristics as potential factors (e.g., Ettema & Schekkerman 2016 ; Weckroth et al, 2022 ). Others conceptualise the relationship between objective living conditions and SWB indirectly by including subjective evaluations of these conditions (McCrea et al, 2006 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The subjective assessment of living conditions is dependent on people’s preferences and values and is thus related to their assessment of their overall well-being. Several researchers therefore highlight the importance of including both types of measures, whenever possible, to create a reliable and complete picture of how living conditions impact SWB (McCrea et al, 2006 ; Pacione, 2003 ; Weckroth et al, 2022 ).…”
Section: Previous Research On Living Conditions and Swbmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, urban populations are also more likely to have access to mental health care, more likely to participate in social organizations which offer psycho-social support (Yang, 2019 ), and more likely to have educational and financial opportunities (Ha, 2019 ), all of which are associated with positive mental health outcomes. A recently published paper assessing quality of life in Finland found higher rates of high quality of life in rural areas but not after controlling for perceived loneliness (Weckroth et al, 2022 ). Another study found that people in urban areas have higher prevalence of both depression and anxiety despite having lower prevalence of other risk factors (Zijlema et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%